Multimode excitation during the inter-ELM-crash periods in KSTAR H-mode plasma. (5th June 2015) - Kim, M.; Lee, J.; Park, H.K.; Yun, G.S.; Lee, W.; Domier, C.W.; N.C., Luhmann
Abstract: Temporal and spatial modulation of the edge localized mode (ELM) structure has been observed during the inter-ELM-crash period by toroidally-separated two electron cyclotron emission imaging systems. The observed modulation is interpreted as a beat wave of two modes with adjacent toroidal mode number. An additional assumption is that each mode has to have a different poloidal rotation speed. In nonlinear simulation, the low- n mode can be driven by locking between the dominant modes. The modulation is reconstructed using beat waves not the locking of modes.